Parallel Tests Using Culture, Xpert MTB/RIF, and SAT-TB in Sputum Plus Bronchial Alveolar Lavage Fluid Significantly Increase Diagnostic Performance of Smear-Negative Pulmonary Tuberculosis - Fan, Lin; Li, Danfeng; Zhang, Shaojun; Yao, Lan; Hao, Xiaohui; Gu, Jin; Li, Hong; Niu, Jinxia; Zhang, Zhemin; Zhu, Changtai (Frontiers in Microbiology, 2018)
At present, tuberculosis remains a serious threat to human health. The diagnosis of pulmonary tuberculosis (PTB) is still difficult, and the prominent challenge for diagnosis is the lack of a highly sensitive and specific method. In order to explore the diagnostic value of parallel tests, this study prospectively enrolled 258 patients with smear-negative PTB from May 2, 2015 to December 31, 2016. The sputum specimens and bronchial alveolar lavage fluid (BALF) samples from all patients were assessed for MTB detection by culture, Xpert MTB/RIF, and SAT-TB. Overall, the sensitivity of any single test using culture, Xpert MTB/RIF, or SAT-TB was lower than that for parallel tests (p < 0.05), and the sensitivity rates for MTB detection in BALF were significantly higher than those in sputum samples. There were lower agreements in the detection results between sputum samples and BALF for all tests (p < 0.05). The parallel tests models of using culture plus Xpert MTB/RIF plus SAT-TB, culture plus Xpert, or culture plus SAT-TB achieved higher sensitivities compared with all three single test models (p < 0.05). Additionally, joint detection using sputum and BALF samples achieved a high sensitivity (0.8566, 95%CI: 0.8086-0.8941). In conclusion, the parallel tests model using culture, Xpert MTB/RIF, and SAT-TB in sputum plus BALF significantly increases the diagnostic performance of smear-negative PTB; thus, this method should be applied clinically when PTB is suspected but smear results are negative.